Optimal Placement of Custom Power Devices in Power System Network to Mitigate Voltage Sag under Faults - D.K. Tanti; M.K. Verma; Brijesh Singh; O.N. Mehrotra (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
Voltage sag has been considered to be a serious power quality problem faced by many utilities. Placement of custom power devices may prove to be an effective remedy for solving power quality problems. In this paper, an Artificial Neural Network (ANN) based approach for optimal placement of Distribution Static Synchronous Compensator (DSTATCOM), Dynamic Voltage Restorer (DVR) and Unified Power Quality Conditioner (UPQC) in a power system network has been considered to mitigate voltage sag under faults. Voltage sag under different type of short circuits has been estimated using MATLAB/SIMULINK software. Optimal location of custom power devices has been obtained using a feed forward neural network trained by post-fault voltage magnitude of three phases at different buses. A comparative performance of DSTATCOM, DVR and UPQC in voltage sag mitigation has been studied to select most effective controller out of three controllers for the system. Case studies have been performed on IEEE 14-bus system. The effectiveness of proposed approach of placement of custom power devices has been established on the test system considered. DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.370